Pengaruh Penggunaan Knalpot Standard dan Knalpot Racing Terhadap Daya dan Torsi pada Motor Supra GTR K56 150 CC - Jaya Saputra, Trisma; Ali Ahmad, Shofiyuddin; Abdullah Ibnu Mas’ud, Hanif; Faizhal, Muhammad; Al Rozaq, Fadel (Rifa'Institute, 2023)
At this time, motorcycles, especially performance, are very important, where many young people now really want to increase the performance of their motorbikes. This study examines the difference in performance between the use of standard exhaust and racing exhaust on a Supra GTR K56 150 cc motorcycle. The experimental method is used by using a dynometer to measure the power and torque of the vehicle. The results showed that the use of racing exhaust resulted in an increase in power of 1.86 hp at 9000 rpm and a widening of the peak power at high engine speed. In addition, the racing exhaust also provides more controlled acceleration and a smoother power increase compared to the standard exhaust. Even though the performance increase is not significant, changing the exhaust to a racing exhaust can give a different response when the vehicle is used at high engine speed. In conclusion, the use of racing exhaust on a 150 cc Supra GTR motorcycle can produce higher performance and better response compared to the standard factory default exhaust.